1981
DOI: 10.1080/02772248109356953
|View full text |Cite
|
Sign up to set email alerts
|

The application of analytical techniques to the understanding of chemical processes occurring in the atmosphere†

Abstract: The science of atmospheric chemistry has expanded enormously over the last decade. In the stratosphere it has become apparent that small traces of a number of gases can perturb the earth's ozone layer. In the troposphere it is now realised that a general oxidation process is occurring which involves several free radicals and a large number of stable gaseous molecules containing the elements H, C, N, O, S, P, F, Cl, Br and I. In areas close to centres of large population this leads to the phenomenon of photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A more direct approach is to consider the atmospheric concentrations of a range of sulphur gases in combination with their chemical behaviour (Sze and Ko, 1980). Building up the sulphur budget from a study of its gaseous precursors has proved possible because of the development of specific methods of analysis (Penkett, 1981) and improved knowledge of the chemistry involved. This has shown that the two most abundant sulphur gases are carbonyl sulphide and sulphur dioxide, which are distributed at relatively constant concentrations throughout the whole of the remote troposphere .…”
Section: Introductionmentioning
confidence: 99%
“…A more direct approach is to consider the atmospheric concentrations of a range of sulphur gases in combination with their chemical behaviour (Sze and Ko, 1980). Building up the sulphur budget from a study of its gaseous precursors has proved possible because of the development of specific methods of analysis (Penkett, 1981) and improved knowledge of the chemistry involved. This has shown that the two most abundant sulphur gases are carbonyl sulphide and sulphur dioxide, which are distributed at relatively constant concentrations throughout the whole of the remote troposphere .…”
Section: Introductionmentioning
confidence: 99%
“…A review article describing the progress in this field has recently been published (37). A review article describing the progress in this field has recently been published (37).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the expanding field of high performance liquid chromatography (HPLC) employs hydrophobic reverse bonded-phase microparticulate column substrates that allow direct equilibrium measurements for modeling lipidwater partition coefficients of sparingly soluble molecules (37). For example, the expanding field of high performance liquid chromatography (HPLC) employs hydrophobic reverse bonded-phase microparticulate column substrates that allow direct equilibrium measurements for modeling lipidwater partition coefficients of sparingly soluble molecules (37).…”
Section: Air or Vapormentioning
confidence: 99%
See 1 more Smart Citation